Blue and Green Infrastructure and the Real Estate Market - Żółtaszek, Agata; Stodulska, Martyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
In recent years, the ecological awareness of Poles has been systematically growing. Approx. 75% of citizens see climate change as a key threat to the lives of people on Earth. Among the most frequently suggested by responders remedial actions is caring for green spaces and watercourses. As a result, the interest of citizens and authorities in the subject of blue‑green infrastructure has also increased. All elements of green infrastructure (GI) and blue infrastructure (BI), as well as their connections, i.e. blue and green infrastructure (BGI), bring health, social, economic and environmental benefits, both in the macro scale (region, country or the whole world) and micro (i.e. in the immediate vicinity of BGI). From the real estate market point of view, it becomes important to investigate whether the awareness of the positive aspects of BGI is reflected in customer demand preferences. If so, it should influence demand decisions, regarding purchase or lease, and the level of transaction prices, as well as supply decisions (construction and development).Therefore, the purpose of this study is to try to identify customer preferences regarding the impact of the proximity of BGI on the demand in the real estate market. The study analyzes the realized demand on the basis of a review of existing research, as well as potential demand using a pilot online questionnaire for a convenient sample. The survey allowed for a preliminary assessment of the subjective preferences of past and potential buyers and tenants of real estate in Poland. Moreover, the availability of GI and BI in Poland was assessed in terms of regions.The results of the analysis showed that the blue and green infrastructure strongly influences the demand on the real estate market in Poland. Respondents appreciate the proximity of green areas and water reservoirs. This determines their noticeable preferences in terms of purchased and rented properties and their willingness to pay for them. This confirms the conclusions of numerous international studies. The presence of green areas and water bodies is location’s prestigious factor, provided, however, that the aesthetic value of the facilities and the distance from them are satisfactory.